2022
DOI: 10.4149/neo_2022_211223n1826
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of neoadjuvant immunochemotherapy for esophageal squamous cell carcinoma and its relationship with expression and changes of PD-L1

Abstract: The alleviation of neoadjuvant immunochemotherapy (NICT) and neoadjuvant chemoradiotherapy (NCRT) was compared for esophageal squamous cell carcinoma (ESCC), and the correlation between the expression and changes of PD-L1 and the efficacy of NICT was evaluated in this study. Fourteen patients with ESCC who received preoperative NICT were included in group A, and fourteen patients with ESCC who received preoperative NCRT were included in group B. Next, group A was divided into CR (complete response), PR (partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Other studies have shown that neoadjuvant immunochemotherapy can upregulate the expression of PD-L1 and TILs [24]. Both neoadjuvant immunochemotherapy and neoadjuvant radiotherapy can upregulate PD-L1 expression [25], which supports our current research ndings.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have shown that neoadjuvant immunochemotherapy can upregulate the expression of PD-L1 and TILs [24]. Both neoadjuvant immunochemotherapy and neoadjuvant radiotherapy can upregulate PD-L1 expression [25], which supports our current research ndings.…”
Section: Discussionsupporting
confidence: 90%
“…After searching for full‐text articles, 51 articles were further excluded because of duplicate publications, a lack of relevant subgroups, incomplete data, or other reasons (e.g., non‐English language). Finally, 27 articles published between 2017 and 2022, 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 were eligible for this meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamic analysis of samples before and after NICT treatment revealed an increase in immune cell populations, especially in responders, reinforcing the link between immune cell accumulation and treatment success ( 37 , 38 ). Interestingly, PD-L1 expression decreased in responders but increased in non-responders post-treatment, suggesting NICT may reinvigorate exhausted T cells, enhancing the immune response ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%